1982
DOI: 10.1111/j.1756-1051.1982.tb01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation in microsporangia of Pinus sylvestris with special attention to the tapetum. I. The pre–and early–meiotic periods

Abstract: The tapetal layer becomes distinct from the other layers of parietal cells about three days prior to the meiosis in the microspore mother cells. Differentiation of the tapetal cells includes an increased relative volume for dictyosomes, mitochondria and plas–tids, the appearance of autophagic vacuoles in the cytoplasm, and periplasmic spaces between the plasma membrane and the cell wall. About one day before the meiosis the basophilia in tapetal cells is elevated; there are numerous nonaggregated ribo–somes, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Differentiation toward a secretory condition prior to meiosis in MMCs, early and mid pachytene, and early diplotene was in each case asynchronous for tapetal cells of a rnicrosporangium. Cell walls were lysed prior to meiosis and thereafter TCs lacked cell walls and, during periods of differentiation, connections between cells (Walles & Rowley 1982, Rowley & Walles 1985. We found that dedifferentiation started asynchronously and was synchronous in conjunction with the formation of tempo-rary plasmodesma-like connections between tapetal cells.…”
Section: Discussionmentioning
confidence: 93%
“…Differentiation toward a secretory condition prior to meiosis in MMCs, early and mid pachytene, and early diplotene was in each case asynchronous for tapetal cells of a rnicrosporangium. Cell walls were lysed prior to meiosis and thereafter TCs lacked cell walls and, during periods of differentiation, connections between cells (Walles & Rowley 1982, Rowley & Walles 1985. We found that dedifferentiation started asynchronously and was synchronous in conjunction with the formation of tempo-rary plasmodesma-like connections between tapetal cells.…”
Section: Discussionmentioning
confidence: 93%
“…The tapetum surrounding microspores acts not only as a nutrient supply (active in the synthesis and transport of proteins, lipids, carbohydrates), but also produces and secretes material utilised in the formation of sporopollenin in pollen walls (Chapman 1987;Mascarenhas 1990;Pacini and Franchi 1993;Pennell and Bell 1986;Rowley and Walles 1985a, 1985b, 1987, 1988Walles and Rowley 1982) and, in some angiosperms, produces pollenkitt and tryphine, which are involved in coating Tapetal cells surrounding the megaspores (Me) of a sterile ovule. Bars 5 m and pigmenting the pollen wall (Mascarenhas 1990).…”
Section: Discussionmentioning
confidence: 99%
“…There are detailed reports of tapetal development for conifer species (Chen et al 1987;Rowley and Walles 1985a, 1985b, 1987, 1988Walles and Rowley 1982); however, there are no reports of tapetal dysfunction leading to male sterility. Male sterility has only been reported in a few conifer species, including Pseudotsuga menziesii (Orr-Ewing 1978), Picea abies (Andersson 1947), and Cryptomeria japonica (Taira 2000), and only the latter study described anatomical detail.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for estimation of volume densities are outlined in Walles and Rowley (1982) and the methodological reference works of Steer (1981), Weibel (1980), andToth (1982). In the present report differentiation is much more dramatic than during earlier stages and can therefore be appreciated for many cytoplasmic structures in even a few selected figures for each phase.…”
Section: Sterometrymentioning
confidence: 95%
“…the six described in Walles and Rowley (1982), which include Nos. 2 and 3 above, plus a 1:l diluted Karnowsky mixture (No.…”
Section: Fixationmentioning
confidence: 98%